The illegitimacy? of the non-peaceful actions by human rights defenders in social conflict contexts - Ancí Paredes, Noemí (2020)
The main objective of this article is to reflect on the legitimacy of the not necessarily peaceful activities of human rights defenders in social conflicto contexts. The paper does not intend to exhaust the reflection by offering some formula that allows us to distinguish between activities that deserve legitimate recognition by the State and those that do not. What it does seek to offer is a set of premises that allow us to project a greater openness towards the exceptional use of non-traditional actions by human rights defenders, circumscribing this possibility to social conflict contexts.